Modelling nitrogen and water stress effects on the growth and yield of choy sum (Brassica chinensis VAR. parachinensis [Bailey]) - Kamarudin, Khairun Nisa (2013)
Choy sum is a leafy vegetable and popular as they are a main source of glucosinolates that functioned as anti-aging, anti-oxidant and anti-cancer effects. This plant is known to accumulate nitrates and more successful during the dry season with the necessary irrigation but still not clearly known the level of the dry condition. Since nitrogen and water arc two main factors that arc dependent on each other. it is important to know the quantity level for optimum on plant growth and yield. This research was conducted to evaluate the growth and yield of choy sum in response to four watering frequencies with amount (once a day, once a week. once every two weeks, and no watering) at five levels of nitrogen rate (0. 34, 68. 136. 272 kg ha. 1 ) and to modify and validate an existing mathematical growth model in response to these stresses. The glasshouse experiment was setup under the rain shelter at Agronomy Research Farm, Universiti Putra Malaysia in split-split pint design with four replications. Water stress was more affected (P<0.05) in regulating growth parameters than nitrogen levels. The leaf area, specific leaf area and root length decreased with increasing of N rate while leaves, shoot and total dry weight. leaf area and shoot-to-roots ratio decreased by increasing of water stress ( less watering). The interaction between both treatments showed that the leaf number decreased when N rate increased and the water stress decreased while the plant height decreased when both of rate and water stress were increased. The nitrogen concentration in choy sum tissues increased with increasing of N rate in well-watered conditions but decreased under water deficit conditions. The choy sum responded more positively with once a week of watering at the N rate of 34 kg ha on leaf number. plant height, leaf area, and leaves dry weight. Hence, there was no requirement for daily or frequent watering and the N rate at 68 kg ha. The choy sum growth model was developed in Microsoft Excel with add-in Buildlt 1.02. The equations involved in this model were arranged in sheets and divided to four main components (weather, photosynthesis, evapotranspiration and maintenance, and growth respiration). The relationship of nitrogen rate among the water stress on the specific leaf area (SLA) was found as Sl/1 = 0.02473 + 0.00087246D.rl T - 0.000040 I 2Nrure where DAT is clay after transplanting and Nrate is nitrogen rate with the maximum of nitrogen rate was found to be 55 kg N ha·' when LAI started to decline. The model validated with five parameters which were dry weight of leaves, stem, and root. leaf area index (LAI) and plant height with the average error were in the range of -44 to 52%, -33.08 to 162.96%, -20.22 to 95.25%, -25.88 to 139.81 %. and -23.46 to 12.68%, respectively. The model still needed some modification to increase the model accuracy.